Urbanization impact on mosquito community and the transmission potential of filarial infection in central Europe - Čabanová, Viktória; Miterpáková, Martina; Valentová, Daniela; Blažejová, Hana; Rudolf, Ivo; Stloukal, Eduard; Hurníková, Zuzana; Dzidová, Marianna (Parasites & vectors, 2018)
BACKGROUND: Despite long-term research on dirofilariosis in Slovakia, little attention has thus far been paid to Dirofilaria vectors. The particular aim of the present study was molecular screening for filarioid parasites in two different habitats of Bratislava, the capital city of Slovakia. In addition, the effect of urbanisation on mosquito species abundance and composition, associated with the risk of mosquito-borne infections, was studied and discussed. METHODS: Mosquitoes were identified by morphological features, and molecular methods were also used for determination of selected individuals belonging to cryptic species from the Anopheles maculipennis and Culex pipiens complexes. The presence of filarioid DNA (Dirofilaria repens, Dirofilaria immitis and Setaria spp.) was detected using standard PCR approaches and sequencing. RESULTS: A total of 6957 female mosquitoes were collected for the study. Overall, the most abundant mosquito species was Aedes vexans, closely followed by unidentified members of the Cx. pipiens complex and the less numerous but still plentiful Ochlerotatus sticticus species. Further investigation of mosquito material revealed 4.26% relative prevalence of Dirofilaria spp., whereby both species, D. repens and D. immitis, were identified. The majority of positive mosquito pools had their origin in a floodplain area on the outskirts of the city, with a relative prevalence of 5.32%; only two mosquito pools (1.26%) were shown to be positive in the residential zone of Bratislava. Setaria spp. DNA was not detected in mosquitoes within this study. CONCLUSIONS: The study presented herein represents initial research focused on molecular mosquito screening for filarioid parasites in urban and urban-fringe habitats of Bratislava, Slovakia. Molecular analyses within the Cx. pipiens complex identified two biotypes: Cx. pipiens biotype pipiens and Cx. pipiens biotype molestus. To our knowledge, Dirofilaria spp. were detected for the first time in Slovakia in mosquitoes other than Ae. vexans, i.e. D. repens in Anopheles messeae and unidentified members of An. maculipennis and Cx. pipiens complexes, and D. immitis in Coquillettidia richiardii and Cx. pipiens biotype pipiens. Both dirofilarial species were found in Och. sticticus. The suitable conditions for the vectors' biology would represent the main risk factor for dirofilariosis transmission.
Keywords: dirofilarióza; komáří přenašeči; Urbanization; Population Dynamics; Dirofilaria; Anopheles; Mosquito-borne diseases; zvířata; Setariasis; Culex; Dirofilaria repens; Slovenská republika; Slovakia; populační dynamika; Dirofilaria immitis; setariáza; Setaria Nematode; Mosquito Vectors; urbanizace; Anopheles maculipennis complex; Xenomonitoring; Setaria (Nematoda); Culex pipiens complex; Animals; Risk Assessment; hodnocení rizik; Dirofilariasis